PENDIDIKAN AGAMA ISLAM DALAM TRANSFORMASI DIGITAL: PENGGUNAAN E-LEARNING, LMS, DAN MEDIA INTERAKTIF - Nasruns; Siarman; Lutia Yunara; Juli Darma Yanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to investigate how Islamic Religious Education isundergoing Digital Transformation: The use of e-learning, LMS, and InteractiveMedia. In addition, this study also aims to identify various challenges andopportunities that arise in the use of digital technology. This study uses a literaturereview. The primary data used in this study was obtained directly from articlesrelated to Islamic Religious Education in Digital Transformation and collectedthrough an open journal system. The results of the study reveal that digitaltransformation through the use of e-learning, LMS, and interactive mediacontributes positively to improving the quality of Islamic Religious Education.Digital technology can expand access, increase flexibility, and make the learningprocess more interesting and interactive. Students have the opportunity to learnindependently while being facilitated in more dynamic academic discussions.However, obstacles in the form of limited infrastructure and educator competenceremain challenges that need to be overcome.